Femur neck fracture in young adults, is it really an urgent surgery indication: Retrospective clinical study - Gümüştaş, Seyit Ali; Tosun, Hacı Bayram; İşyar, Mehmet; Serbest, Sancar; Öznam, Kadir; Bulut, Güven (African Field Epidemiology Network-Afenet, 2018)
Introduction: Femur neck fracture comprises a significant part of intracapsular femur fracture in the intracapsular area of proximal femur and it is mostly seen in elder people. However, these kinds of fractures may be seen in young adults. The present study aims to search factors that affect femoral neck fractures in young adults after surgery carried out by internal determination method. Methods: Files of patients who were applied internal determination through closed reduction and cannulated screw because of intracapsular femur neck fractures between 2010 and 2015 were analyzed retrospectively. Fractures were evaluated by means of Garden classification, which is based on radiological appearance. The cases were examined in terms of timing of surgery in two groups. Cases operated in the first 24 hours after trauma consisted of group 1 and after 24 hours group 2. Radiological staging in femoral head avascular necrosis was evaluated by ficat-Arlet classification system whereas acetabular fractures and hip functionality was evaluated by Letournel and Judet system, which is based on direct graph of fracture line. Results: Mean age at the time of surgery for 31 cases included in the study was 40.04 9.63 year. The average duration from injury to surgery was 6.6 (1-20) days. Thirty nine percent of fractures was nondisplaced whereas 61% was displaced. The average follow-up period was 4.9 1.35 years. The rate of nonunion was found 16% and femoral head avascular necrosis 6.4%. According to Judet System, 67.7% of cases showed excellent/good and 32.3% moderate/bad functional results. Six cases had a secondary surgery. Cases who had displaced fractures statistically showed worse functional results and underwent more secondary surgery than patients with nondisplaced fractures (P>0.05). As a result of logistic regression analysis, presence of displacement was a factor negatively affecting the judet score but did not affect the rate of complication. There were no significant differences between the two groups according to the surgical timing in terms of functional outcomes and complications. Conclusion: Because of surgical treatment of femoral neck fractures in the first 24 hours does not affect functional outcomes and complication rate, surgery is recommended in optimal conditions. In the case of displacement, care must be taken in terms of poor functional results.
WOS: 000437781600002
PubMed ID: 30364439
Keywords: Timing of Surgery; Femoral Neck Fractures; Internal Determination; Complication